THE BURDEN BENEATH THE BURNS: A FIFTY-MONTH RETROSPECTIVE EPIDEMIOLOGICAL STUDY IN EAST NUSA TENGGARA, INDONESIA - Nada Syifa Kasih Widanti; Robertus Arian Datusanantyo (Universitas Airlangga, 2026)
Highlights: Scalds are the leading cause of burn injuries. Major burns affect both children and adults significantly. Electrical burns suggest occupational risk in Southeast Indonesia. Abstract: Introduction: Burn injuries remain a major public health concern, particularly in low- and middle-income countries (LMICs) such as Southeast Indonesia. The lack of long-term, region-specific epidemiological data limits understanding of burn incidence patterns and hinders effective prevention and management strategies. This study aims to address this gap by providing a multi-year epidemiological overview of burn injuries over a 50-month period in East Nusa Tenggara, Indonesia. Methods: A retrospective descriptive study was conducted using medical records of burn patients admitted to plastic surgery departments in three referral hospitals in Kupang, East Nusa Tenggara, from March 2021 to May 2025. Data included patient demographics, burn extent (TBSA), depth, cause, anatomical distribution, and severity categorized according to the American Burn Association criteria. Results: A total of 160 patients met the inclusion criteria, with a slight male predominance (52.5%). The mean age was 39.7 years for males and 36.6 years for females. Most burns involved less than 20% TBSA, with minor burns accounting for the largest proportion in both adults (41.18%) and pediatric patients (41.4%). Scald injuries were the most common cause (41.25%), followed by electrical burns (12.5%) and flame injuries. Adults were more frequently affected by electrical and flame burns, suggesting occupational exposure. Conclusion: Scald burns predominated across age groups, while major burns remained substantial in both children and adults. The relatively high proportion of electrical burns highlights the need for improved workplace safety measures. This multi-year, multi-center study provides one of the first long-term epidemiological datasets from referral hospitals in Eastern Indonesia, addressing a critical evidence gap and offering baseline data to inform targeted prevention strategies and future research on region-specific socio-cultural risk factors.